The effect of phantom sensation on the autocorrelation of gait in amputation - SELÇUK, HALİT (My University, 2023)
Amputation affects the individual\"s entire life with a long rehabilitation and adaptation process. Phantom sensation is the sensing of the presence/position of the limb that existed before but subsequently lost its function. Our research aims to investigate the effect of phantom limb sensation on the autocorrelation of gait in individuals with transtibial amputation. In this context, autocorrelation function (ACF), rescaled range analysis (RRA), and power spectrum density (PSD) evaluations are employed to analyze the acceleration data of gait from the vertical plane. Subjects with unilateral trans-tibial amputation and prostheses were involved in the work. As a result, the gait profile of individuals with phantom sensation for approximately 512 steps on a non-perturbed ground is similar to healthy individuals by the results obtained from all three methods. This shows us that phantom sensation can be a functional part of gait and is a supporting factor for amputees in the adaptation process.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; Yapay Zeka; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Bilgisayar Bilimi Uygulamaları; Artificial Intelligence; Physical Sciences; Computer Networks and Communications; Computer Science Applications; Amputation; Autocorrelation; Gait; Phantom Sensation; Rehabilitation Engineering